Identifying genetic diversity for improved nitrogen-use efficiency and associated physiological traits in wheat (Triticum aestivum L.) and wheat amphidiploids - Nehe, Ajit (2018)
Wheat is one of the most widely consumed staple crops in the world including India and its demand is increasing with increasing population. Increased grain yield (GY) has been associated with increased use of nitrogen (N) fertilizers which represent a significant environmental and production cost. Developing cultivars which have higher grain yield but use N efficiently may allow reduced fertilizer N inputs. The objectives of this study were to: (i) quantify the genetic variability in N use-efficiency (grain dry matter (DM) yield per unit N available from soil and fertilizer, NUE) in a panel of modern Indian wheat cultivars and find new genetic variation in a panel of amphidiploids produced by crossing hexaploid bread wheat with wild wheat relatives and (ii) identify traits and understand physiological mechanisms determining improved NUE to exploit for development of new N efficient cultivars. Thirty Indian elite bread wheat cultivars and 18 amphidiploid lines along with their five respective bread wheat parents were tested under high N (HN) and low N (LN) conditions in two years in field experiments at Agharkar Research Institute, Pune, India (2013 and 2014) and in glasshouse experiments at Nottingham University, UK, (2015 and 2016), respectively. Detailed growth analysis was conducted including GY, above-ground dry matter (AGDM), DM and N partitioning at anthesis and at harvest along with N remobilization efficiency (NRE) in the field experiment. Senescence kinetics of the flag-leaf were assessed from a visual score weekly from anthesis to complete canopy senescence in both sets of experiments. Physiological traits were assessed including flag-leaf light-saturated photosynthetic rate (Amax) under HN conditions in the field experiment and under both HN and LN conditions in glasshouse experiment. Flag-leaf relative chlorophyll content (SPAD) under HN and LN conditions was measured in both experiments; and Normalized Difference Vegetative Index (NDVI) under HN and LN conditions in field experiment. 2D seedling root phenotyping was carried out on subset of 12 genotypes selected based on contrasting performance under LN conditions from both the field and glasshouse experiments. In field experiments, GY was reduced under low N (LN) conditions on average by 1.46 t ha−1 (28%). Crop above-ground N-uptake at harvest on average was reduced from 16.2 kg N ha−1 under HN to 8.5 kg N ha−1 under LN conditions while N-utilization efficiency (grain DM yield per unit above-ground N uptake at harvest; NUtE) increased from 32.7 to 44.6 g DM g−1 N. Significant N × genotype level interaction was observed for GY, N uptake at harvest and NUtE. Overall genetic variability in GY and NUE (which ranged from 15.6 - 23.7 g DM g−1 N under LN; P<0.001) related mainly to differences in N uptake rather than NUtE. Overall, cultivars ranged significantly at anthesis in N accumulation in the flag-leaf N (1.1 -2.2 g N m−2 at HN and 0.5-1.0 g N m−2 at LN), the stem and remaining leaf with sheath (5.78-11.97 at HN and 3.61- 6.33 g N m−2 at LN) (P=0.01), and the ear (2.91-6.13 at HN and 2.06-4.23 g N m−2 at LN) (P<0.001). Cultivars ranged in N partitioning index (proportion of above-ground N in the crop component, NPI) at anthesis for the flag-leaf from 0.08 to 0.16 at HN and 0.07 to 0.13 at LN (P< 0.001); and for the stem-and remaining leaf with sheath from 0.54 to 0.68 at HN and from 0.52 to 0.65 at LN (P<0.001) and for ear from 0.21 to 0.34 at HN and from 0.28 to 0.41 at LN (P<0.001). The post-anthesis NRE was positively associated with the duration of flag-leaf senescence amongst cultivars under LN. Genetic variation in grain yield and grain N% (through N dilution effects) appeared to be mainly influenced by pre-anthesis N accumulation rather than post-anthesis N remobilization under LN conditions. Under N stress conditions, there was evidence that NRE was a determinant of genetic variation in grain N%. Flag-leaf Amax was positively associated with AGDM (P=0.02), GY (P=0.14), and specific leaf N at anthesis (P=0.046). Flag-leaf onset (VS.OnsetRP) and end (VS.EndRP) of senescence was positively associated with GY, AGDM and NRE in both N treatments. In the glasshouse experiments, out of 18 amphidiploid lines, two lines under HN and three lines under LN conditions showed transgressive segregation (TS) above the bread wheat parent for pre-anthesis Amax and 12 lines under HN and 7 lines under LN conditions showed TS for post-anthesis Amax. In addition, higher expression than the bread wheat parent was observed for Thinopyrum turcicum P208/201 x Chinese Spring Eup 94 under HN conditions for GY and for Thinopyrum turcicum P208/201 x Chinese Spring Eup 94, Secale anatolicum P208/142 x Highbury and Secale anatolicum P208/141 x Chinese Spring Eup 94 under HN conditions for AGDM showing potential to exploit these genotypes for wide crossing for NUE wheat breeding. Seedling root architectural traits including seminal root number per plant showed association with field and glasshouse GY and NUE related traits in HN and LN conditions. Overall amphidiploids showed evidence for increased root depth than bread wheat cultivars in the hydroponics seedling platform under both HN and LN conditions. In summary: • N-use efficiency in thirty Indian wheat cultivars in the field was correlated with onset of flag-leaf senescence under high N and low N conditions and senescence timing was correlated with N accumulation at anthesis.